2022
DOI: 10.1039/d2cy00205a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and selective aqueous phase hydrogenation of aryl ketones, aldehydes, furfural and levulinic acid and its ethyl ester catalyzed by phosphine oxide-decorated polymer immobilized ionic liquid-stabilized ruthenium nanoparticles

Abstract: Impregnation of phosphine-decorated styrene-based Polymer Immobilized Ionic Liquid (PPh2-PIIL) with ruthenium (III) trichloride resulted in facile reduction of the ruthenium to afford Ru(II) impregnated phosphine oxide-decorated PIIL (O=PPh2PIIL). The derived...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 139 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…We have recently incorporated heteroatom donors (HAD) into polymer immobilised ionic liquids (PIILs) as supports to stabilise nanoparticles, reasoning that the covalently attached ionic liquid would provide stabilisation through weak electrostatic interactions to the surface of the NP while the heteroatom donor would coordinate to the surface metal atoms and provide additional stabilization to prevent aggregation under the conditions of catalysis [96][97][98][99][100][101][102][103][104]. In addition, the reports described above suggest that modification of immobilized ionic liquids with a heteroatom donor could also enable the surface electronic structure and steric environment to be modified and/or the size and morphology of the NP to be controlled and, as such, HAD-modified polymer immobilised ionic liquids may well be versatile supports for tuning and optimising catalyst performance 105].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently incorporated heteroatom donors (HAD) into polymer immobilised ionic liquids (PIILs) as supports to stabilise nanoparticles, reasoning that the covalently attached ionic liquid would provide stabilisation through weak electrostatic interactions to the surface of the NP while the heteroatom donor would coordinate to the surface metal atoms and provide additional stabilization to prevent aggregation under the conditions of catalysis [96][97][98][99][100][101][102][103][104]. In addition, the reports described above suggest that modification of immobilized ionic liquids with a heteroatom donor could also enable the surface electronic structure and steric environment to be modified and/or the size and morphology of the NP to be controlled and, as such, HAD-modified polymer immobilised ionic liquids may well be versatile supports for tuning and optimising catalyst performance 105].…”
Section: Introductionmentioning
confidence: 99%
“…Our initial endeavours in this area have been extremely promising as PdNPs stabilised by a polyethylene glycol-modified phosphinedecorated PIIL is a remarkably active catalyst for aqueous phase Suzuki-Miyaura cross-couplings [98], the selective hydrogenation of a,b-unsaturated ketones in water [99] and the aqueous phase hydrogenation and transfer hydrogenation of nitroarenes [100], while gold nanoparticles stabilized by a phosphine oxidedecorated polymer immobilised ionic liquid is a highly efficient and selective catalyst for the partial reduction of nitrobenzene to either N-phenylhydroxylamine or azoxybenzene and complete reduction to aniline [101]. Our most recent endeavours in this area have revealed that ruthenium nanoparticles stabilized by the same polymer is a remarkable efficient catalyst for the hydrogenation of aryl and heteroaryl ketones to the corresponding alcohol and levulinic acid to c-valerolactone [102] as well as the hydrolytic evolution of hydrogen from sodium borohydride [103][104]. Herein, we report that RuNP stabilised by a phosphine oxide-decorated polymer immobilised ionic liquid catalyses the partial reduction of a wide range of nitroarenes in ethanol under mild condition and with remarkable efficiency to afford high yields of the corresponding N-arylhydroxylamine with exceptional selectivity (>99 %); in stark contrast, the corresponding AuNP-based system catalyses the sodium borohydride-mediated reduction of nitrobenzene in ethanol to give quantitative conversion to azoxybenzene as the sole product (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The polymers required for this study were prepared via radical polymerisation of the corresponding imidazolium-based ionic liquid monomer, either styrene, (4-vinylphenyl)methanamine or diphenyl(4-vinylphenyl)phosphine oxide and the corresponding imidazoliumbased ionic liquid cross-linker in the ratio x = 1.84, y = 1.0 and z = 0.16, as previously described [119][120][121][122][123]. Catalysts 2a-f were prepared by the wet impregnation of the polymer support with ruthenium trichloride to afford precursors with a 1:1 ratio of ruthenium to neutral monomer, followed by in-situ reduction of the ruthenium with NaBH 4; to afford the product as a fine black powder in high yield; the synthesis and composition of the polymers and the catalysts is shown in Fig.…”
Section: Catalyst Synthesis Characterisation and Runp-catalyzed Hydro...mentioning
confidence: 99%
“…Our early studies showed that palladium nanoparticles immobilized on a polyethylene glycol-modified phosphine-modified PIIL is a remarkably efficient catalyst for aqueous phase Suzuki-Miyaura cross-couplings [119], the chemoselective hydrogenation of α,β-unsaturated ketones, nitriles and esters, [120] and the hydrogenation of nitroarenes [121]. Moreover, gold nanoparticles stabilized by a phosphine oxide-modified polymer immobilised ionic liquid catalyses the highly selective reduction of nitroarenes to afford N-arylhydroxylamines and azoxyarenes [122] and the corresponding ruthenium nanoparticles catalyse the aqueous phase hydrogenation of aryl and heteroaryl ketones and levulinic acid with remarkable efficacy and selectivity [123].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research demonstrated the advantage of phosphine oxide for improved chemoselectivity by creating more polarity to the support, in contrast to triphenyl phosphine. 20 Also, Van Leeuwen et al described phosphine oxide-stabilized metal nanoparticles creating a frustrated Lewis pair, which signifies a strong interaction between metal and bulky phosphine oxide ligand. 21 The formation of an H 2 -ion pair is responsible for chemoselective hydrogenation of the carbonyl group through a concerted approach.…”
mentioning
confidence: 99%